2014
DOI: 10.5607/en.2014.23.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic Lateral Sclerosis - Cell Based Therapy and Novel Therapeutic Development

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease, characterized by the predominant loss of motor neurons (MNs) in primary motor cortex, the brainstem, and the spinal cord, causing premature death in most cases. Minimal delay of pathological development by available medicine has prompted the search for novel therapeutic treatments to cure ALS. Cell-based therapy has been proposed as an ultimate source for regeneration of MNs. Recent completion of non-autologous fetal spinal stem cell transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Amyotrophic lateral sclerosis (ALS), the most common adult onset motor neuron disease, is pathologically characterized by progressive loss of the upper and lower motor neurons in the brainstem motor nuclei and the anterior horn of the spinal cord [12]. This pattern of neurodegeneration produces progressive weakness, muscular wasting, and spasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS), the most common adult onset motor neuron disease, is pathologically characterized by progressive loss of the upper and lower motor neurons in the brainstem motor nuclei and the anterior horn of the spinal cord [12]. This pattern of neurodegeneration produces progressive weakness, muscular wasting, and spasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Over expression of σ1R for this missense mutation (p.E102Q) in NSC34 cells illustrated boosted ER stress leading to increased cell apoptosis [23]. Most recently, a 3′-UTR variant of SIGMAR1 (c.*58 T>C) was reported in sALS of Korean population and was considered as a rare variant [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, C9ORF72 repeat expansions were reported in FTLD and fALS [17,18]. Most recently, a 3′-UTR variant of SIGMAR1 was reported in sporadic ALS of Korean population [19].…”
Section: Introductionmentioning
confidence: 99%
“…A clinical study projected to analyze if transplantation of fetal olfactory ensheathing cells will influence the evolution of disease in patients with ALS, showed that transplantation of olfactory cells are capable to slow, based on clinical findings, the rate of progression within the first four months after transplantation 43 . The authors of another study found that seriate treatment involving multiple injection is safe and feasible, despite the fragility of spine in ALS with observation of functional improvement after treatment 44,45 . There are different experimental models using OECs for Parkinson's disease.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%